Physical and mechanical properties of membrane polyvinilidene flouride with the addition of silver nitrate - Mataram Agung; Rizal S.; Pujiono Estu (MATEC Web of Conferences, 2018)
The membrane is a layer formed from fine fibers are used as a filter. In this research, measured the tensile strength and pore size of the membrane that is made in three variations of a specimen with a mixed composition of different Polyvinilidene Fluoride 17.5%, 20%, 22.5%., membrane made using Polyvinilidene Fluoride polimer granules and N,N-Dimethylformamide as solvent and silver nitrate. Membrane molded into standardized test specimens and tested with a device Adhesion Tearring Strength Tester. The results show an increase in the value of the tensile test of 404.8356 KPa to the composition of 17.5%, 507.3598 KPa for composition of 20% and 603.7218 KPa to a composition of 22.5%. For testing the microstructure using a Scanning Electron Microscopy with the resulting increase in pore diameter, for the range of 558.4 nm-781.8 nm are void to the composition of 17.5%, range 670.1 nm - 781.8 nm without voids for the composition of 20% and 1.117 μm-1.228μm without voids on a composition of 22.5